2014
DOI: 10.1002/he.20079
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Learning Model: How College Students Integrate Learning

Abstract: Students integrate their learning experiences across contexts through a process of connecting, applying, and synthesizing information, knowledge, and skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 7 publications
2
33
0
Order By: Relevance
“…Our findings lend particular support to Barber's (2014) first and third points. We found that often students were unable to integrate learning across very different contexts because they were unable to see the similarities between or among those contexts.…”
Section: Facilitators Of and Barriers To Integrationsupporting
confidence: 80%
See 3 more Smart Citations
“…Our findings lend particular support to Barber's (2014) first and third points. We found that often students were unable to integrate learning across very different contexts because they were unable to see the similarities between or among those contexts.…”
Section: Facilitators Of and Barriers To Integrationsupporting
confidence: 80%
“…In discussing some of the reasons why students might not engage in integration, Barber (2014) explained, "Three of the key issues facing students in regard to learning are (a) compartmentalization, (b) the ever-increasing collection of digital tools available, and (c) a lack of opportunities for reflection" (p. 12). Our findings lend particular support to Barber's (2014) first and third points.…”
Section: Facilitators Of and Barriers To Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical deficits in learning at this level include: failure to learn from experience (Kolb, 1984(Kolb, , 1998Presley & Leslie, 1999;Rowley, Lujan, & Dolence, 1997); failure to pool knowledge across disciplines, departments, and administrative units (Barber, 2014;Lauer, 2006); and failure to monitor plans and tweak performance (Holcomb, 2001;Wilson, 1997). As evidenced in the chapters of this volume, a lack of support for making connections and integrating topics hinders learning at all levels.…”
Section: Shannon M Chancementioning
confidence: 99%